The doctrine of solidism and neurology in the first half of the 19th century in Vilnius - E. Sakalauskaitė-Juodeikienė (Neurologijos seminarai)
In the first half of the 18th century, European medical literature was pervaded with fibre-related terms such as “membranes”, “web”, “vibrating”, “folding”, “tone”, “tension”, etc. The doctrine of humoralism which attributed all diseases to imbalance of the four humours was gradually replaced by a new doctrine of solidism suggesting that fibres were the most important building units of the body. How was the doctrine of solidism received and how did it change the perception and diagnosis of nervous system diseases in the first half of the 19th century in Vilnius? After analysing several doctoral dissertations, written in Latin and defended at Imperial University of Vilnius, we came to the conclusion that the causes of nervous system diseases were mostly sought in the cerebrum and spinal cord, using autopsy findings as an essential part of the anatomo-clinical method, under the influence of the principles of the doctrine of solidism.